Effect of diffusive Nb redistribution on the pitting susceptibility of U-5.5Nb alloys. (1st April 2020) - Chen, Xianglin; Ji, Hefei; Zhao, Yawen; Wu, Yanping; Lu, Chao; Zhang, Yanzhi; Shi, Peng; Meng, Daqiao
Highlights: Microstructural characteristics and Volta potentials of U5.5Nb alloys were evaluated. Isothermal aging redistributes the Nb contents in pearlitic lamellae. Preferential pitting occurs at Nb-depleted lamellae because of low Volta potentials. The pitting potential does not change with the content of Nb-depleted lamella. Abstract: The influence of diffusive Nb redistribution on the microstructure and Volta potential of U-5.5Nb alloys thermally aged at 400 °C for durations between 1 h and 100 h was investigated and their surfaces were examined post-corrosion using various microscopy techniques. The results demonstrated that Nb-depleted lamellae resulting from Nb redistribution have the lowest Volta potential in the microstructure and are extremely sensitive to pitting, as demonstrated by immersion experiments and potentiometric polarization tests. However, the pitting potential of the aged alloys (205.2 ± 3.9 mV) did not change with the content of Nb-depleted lamellae.